Magnetic body structure, preparation method thereof and electronic equipment

By filling resin in the holes of the Fe-based soft magnetic alloy powder magnetic body and setting a film layer, the problems of insufficient mechanical strength, poor insulation performance and rust caused by the holes during sintering are solved, and higher magnet strength and insulation performance are achieved, extending the service life of the product.

CN119920563AActive Publication Date: 2025-05-02DONGGUAN SUNLORD ELECTRONICS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411927864.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-05-02
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The holes generated by Fe-based soft magnetic alloy powder during sintering lead to insufficient mechanical strength of the magnet, poor insulation performance, prone to rust and popcorn, affecting the reliability and service life of the product.

Method used

By filling the holes in the magnetic body body with resin and providing a film layer on the surface, the holes are blocked, the insulation performance is improved, and rust is prevented.

Benefits of technology

It enhances the overall strength and insulation performance of the magnetic structure, prevents rust and popcorn, and improves the reliability and service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920563A_ABST
    Figure CN119920563A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic body structures, in particular to a magnetic body structure, a preparation method thereof and electronic equipment. The invention discloses a magnetic body structure, which comprises a magnetic body main body formed by sintering soft magnetic alloy powder; the resin is filled in the hole of the magnetic body main body; the film layer is arranged on the surface of the magnetic body main body; the structure of the magnetic body meets the condition that the strength of the magnetic body is larger than 120N and / or the resistance is larger than 100k omega. According to the magnetic body structure, the resin is filled in the hole of the magnetic body main body to block the hole of the magnetic body main body, and the film layer is arranged on the surface of the magnetic body; the problems of insufficient mechanical strength, poor insulation performance, easy rusting and popcorn phenomena and the like caused by holes in the traditional manufacturing process of the magnetic body structure are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic structures, and in particular to a magnetic structure and a preparation method thereof and electronic equipment. Background Art

[0002] With the rapid development of the electronic components industry, high-current, miniaturized, and high-efficiency electronic components have become the core trend of current product design. In this context, the rapid growth of the AI ​​server market has put forward higher performance requirements for magnetic components such as power inductors, such as high reliability, high saturation characteristics, and low loss. In order to meet these needs, the selection and preparation technology of magnetic materials are constantly innovating. Fe-based soft magnetic alloy powders have gradually replaced traditional ferrite materials due to their excellent electromagnetic properties and machinability, becoming the first choice for high-performance magnetic components.

[0003] However, Fe-based soft magnetic alloy powders face the following adjustments during the preparation process. First, during the high-temperature sintering process, the atoms in the alloy powder will rearrange to form a crystalline structure, and at the same time, the resin and other organic matter contained in the powder will decompose to produce holes of varying sizes. These holes will not only reduce the mechanical properties of the magnet, such as strength and toughness, but also become channels for impurities such as water vapor and dust to invade, resulting in insulation failure of the magnet, rust, and the occurrence of popcorn phenomenon, which seriously affects the reliability and service life of the product.

[0004] In response to the above problems, the current solutions are mainly concentrated in two aspects: one is to reduce the generation of holes by optimizing the sintering process parameters, such as lowering the sintering temperature, extending the insulation time, etc.; the other is to use post-processing processes, such as surface coating and impregnation, to encapsulate and protect the magnets. However, although optimizing the sintering process can reduce the number of holes to a certain extent, it often comes at the expense of electromagnetic performance, and it is impossible to completely eliminate the holes. Although methods such as surface coating and impregnation can improve the insulation and rust resistance of the magnet, the bonding force between the coating and the magnet matrix is ​​weak, and it is easy to fall off when subjected to force or temperature changes, thus affecting the long-term stability of the product.

[0005] In addition, existing technologies still face great difficulties in preparing magnetic structures with no holes or low porosity. On the one hand, the formation mechanism of holes during high-temperature sintering is complex and difficult to fully control through simple process adjustments; on the other hand, post-processing processes often require the formation of a thicker coating on the surface of the magnet, which not only increases the volume and weight of the product, but may also have an adverse effect on the electromagnetic performance.

[0006] Therefore, developing a magnetic structure and its preparation method and electronic equipment that can effectively improve the strength and insulation capacity of the magnet, solve the rust and popcorn problems of the magnet, and at the same time not affect the bonding strength of the outer coating has become a technical problem that needs to be solved urgently. Summary of the invention

[0007] The present application discloses a magnetic structure, a preparation method thereof and an electronic device. By filling the holes of the magnetic body with resin to seal the holes of the magnetic body and providing a film layer on the surface of the magnetic body, the problems of insufficient mechanical strength, poor insulation performance, and easy rust and popcorn phenomenon caused by the holes in the magnetic structure in the traditional manufacturing process are solved.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present application provides a magnetic structure, comprising:

[0010] The magnetic body is formed by sintering soft magnetic alloy powder;

[0011] Resin, filling the holes of the magnetic body;

[0012] A film layer is arranged on the surface of the magnetic body;

[0013] The magnetic structure satisfies: magnetic strength>120N and / or resistance>100kΩ.

[0014] In some specific embodiments, the resin is any one or more of phenolic resin, epoxy resin, silicone resin, acrylic resin, and imide resin.

[0015] In some specific embodiments, the resin is distributed in the magnetic body to a depth of ≥30 μm.

[0016] In some specific embodiments, the thermal expansion coefficient of the resin is less than 1.0 ppm / °C.

[0017] In some specific embodiments, the thickness of the film layer is ≥1 μm and / or the dry-to-touch time of the film layer is ≤20 min.

[0018] In some specific embodiments, the thickness of the film layer is ≥3 μm; and / or the dry-to-touch time of the film layer is ≤10 min.

[0019] In some specific embodiments, a coating layer is further disposed on the film layer.

[0020] In some specific embodiments, the soft magnetic alloy powder is Fe-based soft magnetic alloy powder.

[0021] In a second aspect, the present application provides a method for preparing the magnetic structure according to the first aspect, comprising the following steps:

[0022] The resin is introduced into the pores of the magnetic body by vacuum pressure impregnation, and the resin is formed into a film layer on the surface of the magnetic body by centrifugation.

[0023] In a third aspect, the present application provides an electronic device, comprising the magnetic structure described in the first aspect or the magnetic structure prepared by the preparation method described in the second aspect.

[0024] The beneficial effects of this application are:

[0025] The magnetic structure described in the present application can reduce the magnetic flux leakage caused by the holes generated during the sintering process by filling the holes of the magnetic body with resin, thereby enhancing the overall strength of the magnetic structure; the film layer provided on the surface of the magnetic body can improve the insulation performance of the magnetic structure and prevent current leakage. At the same time, the film layer can isolate moisture and oxygen in the air, prevent the magnetic body from rusting, and extend the service life of the product. Therefore, the present application improves the magnetic strength and insulation performance of the magnetic structure, prevents rust and popcorn phenomenon, and can improve the reliability of the product and the yield rate of the process.

[0026] The preparation method described in the present application introduces the resin into the pores of the magnetic body by means of vacuum pressure impregnation, which can reduce the pores or reduce the gaps between the pores, thereby reducing magnetic flux leakage and improving the mechanical strength and magnetic properties of the magnetic structure; at the same time, the film layer formed by the resin on the surface of the magnetic body can improve the insulation performance of the magnetic structure and prevent current leakage.

[0027] The electronic device described in the present application can improve the performance of components such as power inductors in electronic devices by using a magnetic structure with enhanced magnetic strength and insulation capability, thereby meeting the development needs of high current, miniaturization, and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0029] Figure 1 It is a structural schematic diagram of the magnetic structure of the present invention.

[0030] Among them: 1-magnetic body; 2-resin; 3-film layer; 4-metal particles; 5-coating layer; 6-holes. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0032] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0033] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0034] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0035] The raw materials or reagents used in the embodiments of the present invention and the comparative examples are all purchased from mainstream manufacturers in the market. The manufacturer or concentration is not specified, and they are all analytically pure raw materials or reagents that can be routinely obtained. As long as the expected effect can be achieved, there is no particular restriction. The instruments and equipment used in the present embodiment are all purchased from major manufacturers in the market. As long as the expected effect can be achieved, there is no particular restriction. If specific techniques or conditions are not specified in the present embodiment, the techniques or conditions described in the literature in this area or according to the product specification are carried out.

[0036] Terminology explanation:

[0037] The coefficient of thermal expansion refers to the degree to which a material changes in volume when the temperature rises or falls. For magnetic structures, it is crucial to select a suitable resin material to match the thermal expansion characteristics of the magnetic body. Especially in a working environment where the temperature changes frequently or greatly, the difference in the coefficient of thermal expansion may cause a series of negative effects.

[0038] Metal particles refer specifically to metal particles dispersed in the structure of a magnetic body, usually iron or other metal components in Fe-based soft magnetic alloy powder. The presence of metal particles during the sintering process is one of the reasons for the formation of voids.

[0039] In order to solve the problems of insufficient mechanical strength, poor insulation performance, and easy rust and popcorn phenomenon caused by holes in the traditional manufacturing process of magnetic structures, the present application provides Figure 1 A magnetic structure shown includes:

[0040] The magnetic body 1 is formed by sintering soft magnetic alloy powder;

[0041] Resin 2, filled in the holes 6 of the magnetic body 1;

[0042] A film layer 3 is arranged on the surface of the magnetic body 1;

[0043] The magnetic structure satisfies: magnetic strength>120N and / or resistance>100kΩ.

[0044] Specifically, the above technical solution effectively enhances the overall structural strength of the magnetic structure by filling the pores of the magnetic body with resin, solving the problem of insufficient mechanical strength caused by the pores. The film layer is formed by the resin on the surface of the magnetic body, which can significantly improve the insulation resistance and reduce the risk of short circuit caused by water vapor intrusion. Therefore, the magnetic structure satisfies: magnetic strength>120N and / or resistance>100kΩ.

[0045] Through the above technical solution, the resin-filled holes can prevent external moisture from entering the interior of the magnetic body, avoiding rust and the popcorn phenomenon that may occur during patching, thereby greatly improving the long-term stability and reliability of the product.

[0046] It can be understood that the magnetic structure satisfies the requirements of magnetic strength>120N and / or resistance>100kΩ, so that the magnetic structure reaches high standards in terms of mechanical strength and electrical insulation, meeting the requirements of high-end applications.

[0047] In one or more embodiments, the soft magnetic alloy powder is Fe-based soft magnetic alloy powder, which can provide the magnetic properties required for the magnetic structure, including high saturation magnetic induction intensity and low loss characteristics.

[0048] Specifically, the Fe-based soft magnetic alloy powder is mainly composed of iron (Fe), and other elements such as silicon (Si), aluminum (Al), chromium (Cr), etc. may be added in a certain proportion as needed to adjust its physical and electromagnetic properties.

[0049] It is understandable that during the sintering process of the Fe-based soft magnetic alloy powder, gaps and expansion and contraction between the metal particles 4 result in pores 6 in the magnetic body 1 after sintering. The pores exist inside and on the surface of the magnetic body.

[0050] In one or more embodiments, the resin is any one or more of phenolic resin, epoxy resin, silicone resin, acrylic resin, and imide resin. The specific resin type can be selected according to actual needs.

[0051] In actual applications, the magnetic structure may experience large temperature fluctuations. If the thermal expansion coefficient of the resin material is too high, it may cause uneven thermal stress between the resin and the magnetic body, which may cause deformation or damage to the magnetic structure. Therefore, in the present application, the thermal expansion coefficient of the resin is less than 1.0ppm / ℃, that is, the thermal expansion coefficient of the resin is required to be low, and when the low thermal expansion coefficient surface is used in different temperature environments, the match between the resin and the magnetic body is higher, reducing the risk of damage caused by thermal cycling, thereby improving the long-term reliability and service life of the product. Therefore, in the present application, by selecting a resin with a thermal expansion coefficient of less than 1.0ppm / ℃, the dimensional stability of the magnetic structure can be maintained when the temperature changes, avoiding stress and deformation caused by thermal expansion and contraction, and greatly reducing the risk of deformation or damage to the magnetic structure.

[0052] Specifically, the thermal expansion coefficient of the resin can be any value among 0.75ppm / ℃, 0.80ppm / ℃, 0.85ppm / ℃, 0.88ppm / ℃, 0.90ppm / ℃, 0.95ppm / ℃, and it only needs to be less than 1.0ppm / ℃

[0053] In one or more embodiments, the thickness of the film layer is ≥1 μm, and the dry-to-touch time is ≤20 min.

[0054] Specifically, the film layer thickness is ≥1μm, for example, it can be any value among 1μm, 1.5μm, 2μm, and 2.5μm; the film layer thickness ≥1μm can ensure that the resin material can fully cover the surface of the magnetic body, forming a continuous and dense protective layer, effectively blocking the holes and improving the insulation performance.

[0055] The dry-to-touch time is ≤20 minutes. The resin can be cured in a shorter time, which reduces the processing cycle, improves the turnover rate of the production line, and reduces production costs. The specific dry-to-touch time can be any value among 20 minutes, 19 minutes, 18 minutes, and 17 minutes.

[0056] Preferably, the thickness of the film layer is ≥3 μm, for example, it can be any value among 3 μm, 3.5 μm, 4 μm, and 4.5 μm; the dry-to-touch time of the film layer is ≤10 min, for example, it can be any value among 10 min, 9 min, 8 min, and 7 min.

[0057] In one or more embodiments, a coating layer 5 is further provided on the film layer 3 .

[0058] Specifically, the film layer formed by the current resin has provided preliminary anti-rust protection, but there may still be corrosion risks in certain extreme environments (such as high humidity, salt spray, etc.). The presence of the coating layer provides a double protection barrier for the magnetic body, significantly reducing the possibility of rust and corrosion. The coating layer can be formed after curing epoxy resin or polyurethane.

[0059] More specifically, epoxy resin is often used for coating electronic components due to its excellent adhesion and electrical insulation properties. It can undergo cross-linking reactions with active groups in the underlying resin during high-temperature curing to form a strong interface bond.

[0060] Polyurethane: has good flexibility and chemical resistance, suitable for applications requiring impact or abrasion resistance.

[0061] In one or more embodiments, the resin is distributed in the magnetic body to a depth of ≥30 μm.

[0062] Specifically, Fe-based soft magnetic alloy powder will form holes of varying sizes during the sintering process. These holes weaken the mechanical strength of the magnetic body. By filling the holes with resin, the resin distribution depth reaches ≥30μm, for example, it can be any value among 30μm, 33μm, 35μm, 40μm, and 45μm. The resin distribution depth reaches ≥30μm, which can effectively block these holes and prevent the invasion of water vapor and other harmful substances, thereby improving the overall structural strength and stability of the magnetic structure. After the resin is filled to a certain depth, it can significantly improve the mechanical properties of the magnetic structure, such as compression and tension, and solve the problem of insufficient mechanical strength caused by holes. In addition, the resin filling is not limited to the surface, but penetrates deep into the magnetic body, forming a more complete insulation barrier, reducing the risk of short circuits, and improving the overall insulation effect.

[0063] It can be understood that the internal distribution depth refers to the depth reached by the resin filled in the pores of the magnetic body in the magnetic structure. For example, the depth is the vertical distance between the resin filled in the pores of the magnetic body and the surface of the magnetic body.

[0064] In addition, the present application provides a method for preparing the magnetic structure described above, comprising the following steps:

[0065] The resin is introduced into the pores of the magnetic body by vacuum pressure impregnation, and the resin is formed into a film layer on the surface of the magnetic body by centrifugation.

[0066] Specifically, during vacuum pressure impregnation, the vacuum degree is set to > -0.085Mpa to ensure that the air is fully removed and create conditions for the resin to enter; the vacuum time is set to 30±5 seconds to ensure sufficient vacuum treatment time to empty the air in the pores; the impregnation time is set to > 10 minutes to give the resin enough time to penetrate into the internal pores of the magnetic body.

[0067] After the vacuum impregnation is completed, positive pressure is applied again, the positive pressure is greater than 0.3Mpa, to push the resin to overcome the influence of surface tension and enter deeper holes;

[0068] After the positive pressure is applied, the resin on the surface of the magnetic body is separated. The separation speed is set to 900±100r / min and the separation time is set to 300±30s. The residual amount of resin on the surface of the magnetic body is controlled to form a continuous film on the surface of the magnetic body without affecting the size of the finished product and reducing costs.

[0069] At the same time, the present application provides an electronic device, comprising the magnetic structure described above.

[0070] In this application, the magnetic structure has higher strength, better insulation performance, better rust resistance and long-term stability, which can significantly improve the overall performance and reliability of electronic equipment, thereby enhancing the market competitiveness of the product. Specific electronic equipment may include AI servers, automotive electronics, and consumer electronics.

[0071] AI server: requires high reliability, high saturation characteristics, low loss, etc. The magnetic structure of this application can meet these strict requirements and improve the stability and performance of the server.

[0072] Automotive electronics: They need to remain stable under extreme temperature and humidity conditions. The improvement in the magnetic structure of this application improves its weather resistance and long-term reliability.

[0073] Consumer electronic products: such as smart phones, tablet computers, etc., have high requirements for miniaturization and high performance. The magnetic structure of this application helps to achieve more compact design and higher performance.

[0074] The magnetic structure of the present invention is further described below in conjunction with specific embodiments and comparative examples:

[0075] Example 1

[0076] A magnetic structure, comprising:

[0077] The magnetic body is formed by sintering soft magnetic alloy powder;

[0078] Resin, filling the holes of the magnetic body;

[0079] A film layer is arranged on the surface of the magnetic body;

[0080] The resin has a distribution depth of 30 μm inside the magnetic body; the thermal expansion coefficient of the resin is 0.95 ppm / °C; the thickness of the film layer is 1 μm, and the dry-to-touch time is 10 minutes.

[0081] Example 2

[0082] A magnetic structure, comprising:

[0083] The magnetic body is formed by sintering soft magnetic alloy powder;

[0084] Resin, filling the holes of the magnetic body;

[0085] A film layer is arranged on the surface of the magnetic body;

[0086] The distribution depth of the resin in the magnetic body is 35 μm; the thermal expansion coefficient of the resin is 0.90 ppm / °C; the thickness of the film layer is 1.5 μm, and the dry-to-touch time is 9 minutes.

[0087] Example 3

[0088] A magnetic structure, comprising:

[0089] The magnetic body is formed by sintering soft magnetic alloy powder;

[0090] Resin, filling the holes of the magnetic body;

[0091] A film layer is arranged on the surface of the magnetic body;

[0092] The distribution depth of the resin inside the magnetic body is 38 μm; the thermal expansion coefficient of the resin is 0.85 ppm / °C; the thickness of the film layer is 1.8 μm, and the dry-to-touch time is 9 minutes.

[0093] Example 4

[0094] A magnetic structure, comprising:

[0095] The magnetic body is formed by sintering soft magnetic alloy powder;

[0096] Resin, filling the holes of the magnetic body;

[0097] A film layer is arranged on the surface of the magnetic body;

[0098] The distribution depth of the resin in the magnetic body is 40 μm; the thermal expansion coefficient of the resin is 0.83 ppm / °C; the thickness of the film layer is 2.0 μm, and the dry-to-touch time is 8 minutes.

[0099] Comparative Example 1

[0100] A magnetic structure, the thermal expansion coefficient of the resin is 1.5 ppm / °C; the other conditions are the same as those in Example 1.

[0101] Comparative Example 2

[0102] A magnetic structure, wherein the resin is distributed to a depth of 15 μm inside the magnetic body; and other conditions are consistent with those in Example 1.

[0103] Comparative Example 3

[0104] A magnetic structure, the thickness of the film layer is 0.3 μm; other conditions are consistent with those in Example 1.

[0105] The above-mentioned embodiments 1-4 and comparative examples 1-3 use the same batch and the same model of magnetic body; the size of the magnetic body is 9.0*8.0*2.3mm; the magnetic body is formed by sintering Fe-based soft magnetic alloy powder; the resin used is phenolic resin; the specific method for preparing the magnetic body structure includes the following steps:

[0106] Under the conditions of vacuum degree > -0.085Mpa and vacuum time of 30±5 seconds, first remove the gas in the pores of the magnetic body and introduce the resin into the pores inside the magnetic body; after the resin fills the pores, the resin is allowed to enter deeper pores under a pressure of 0.3Mpa; after the positive pressure is applied, the resin on the surface of the magnetic body is separated, and the separation speed is set to 900±100r / min and the separation time is set to 300±30s to form a continuous film layer on the surface of the magnetic body.

[0107] The magnetic structures prepared in Examples 1-4 and Comparative Examples 1-3 were tested for magnetic strength and resistance, and the test results are summarized in Table 1; the magnetic strength was obtained by testing the core folding strength using an automatic push-pull testing machine; the resistance value was obtained by testing using a resistance meter.

[0108] Table 1

[0109] Group Magnet strength (N) Resistance (kΩ) Example 1 145.3 155.2 Example 2 178.8 183.3 Example 3 221.9 218.6 Example 4 269.9 252.6 Comparative Example 1 144.7 153.9 Comparative Example 2 98.4 149.3 Comparative Example 3 137.5 116.7 Magnetic body 78.6 51.8

[0110] From Table 1, we can see that:

[0111] From Example 1 to Example 4, the magnetic strength of the magnetic structure is 145.3N, 178.8N, 221.9N and 269.9N, respectively, which shows that as the distribution depth of the resin inside the magnetic body increases and the thermal expansion coefficient of the resin decreases, the magnetic strength gradually increases. This is because the resin fills the internal pores of the magnetic body, enhancing the overall structural strength of the magnetic structure, and the resin with a low thermal expansion coefficient helps to reduce the stress and deformation risk caused by temperature changes, thereby improving the mechanical strength of the magnetic structure.

[0112] At the same time, from Example 1 to Example 4, the resistance values ​​of the magnetic structure are 155.2kΩ, 183.3kΩ, 218.6kΩ and 252.6kΩ, respectively. Since the continuous film layer formed after the resin fills the holes effectively isolates the direct contact between the metal particles, the insulation path length is increased, and the possibility of current leakage is reduced, thereby improving the overall insulation performance of the magnetic structure.

[0113] The magnetic structure of Comparative Example 1 has a magnetic strength of 144.7N and a resistance of 153.9kΩ. Compared with Example 1, the magnetic strength of Comparative Example 1 is slightly lower, and the resistance is also slightly lower. Because the thermal expansion coefficient of the resin used in Comparative Example 1 is 1.5ppm / ℃, which is significantly higher than 0.95ppm / ℃ in Example 1, the higher thermal expansion coefficient may cause uneven thermal stress between the resin and the magnetic body, causing deformation or damage of the structure when the temperature changes, thereby affecting the overall strength and insulation performance of the magnetic structure.

[0114] The magnetic strength of the magnetic structure of Comparative Example 2 is 98.4N, and the resistance is 149.3kΩ; the magnetic strength of Comparative Example 2 is significantly lower than that of Example 1, while the resistance is slightly lower. Because the distribution depth of the resin in the magnetic body of Comparative Example 2 is only 15μm, which is much smaller than 30μm in Example 1, the shallower resin distribution cannot effectively block the internal pores, resulting in a significant decrease in the mechanical strength of the magnetic structure, and the presence of the pores increases the risk of current leakage, thereby reducing the resistance.

[0115] The magnetic strength of the magnetic structure of Comparative Example 3 is 137.5N, and the resistance value is 116.7kΩ; the magnetic strength of Comparative Example 3 is slightly lower than that of Example 1, but its resistance value is significantly lower. The film thickness in Comparative Example 3 is only 0.3μm, which is much lower than 1μm in Example 1. Because the too thin film layer cannot provide sufficient protection, it is not enough to completely cover the surface of the magnetic body and form a continuous and dense insulation barrier, so it fails to effectively improve the insulation performance, resulting in a low resistance value. At the same time, although the thin film layer may not directly affect the mechanical strength of the magnetic structure, its magnetic strength is also reduced due to the poor stability of the overall structure.

[0116] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A magnetic structure, characterized in that: include: The magnetic body is formed by sintering soft magnetic alloy powder; Resin, filling the holes of the magnetic body; A film layer is arranged on the surface of the magnetic body; The magnetic structure satisfies: magnetic strength>120N and / or resistance>100kΩ.

2. The magnetic structure according to claim 1, characterized in that: The resin is any one or more of phenolic resin, epoxy resin, silicone resin, acrylic resin and imide resin.

3. The magnetic structure according to claim 1, characterized in that: The resin is distributed in the magnetic body to a depth of ≥30 μm.

4. The magnetic structure according to claim 1, characterized in that: The thermal expansion coefficient of the resin is less than 1.0 ppm / °C.

5. The magnetic structure according to claim 1, characterized in that: The thickness of the film layer is ≥1 μm and / or the touch drying time of the film layer is ≤20 min.

6. The magnetic structure according to claim 5, characterized in that: The thickness of the film layer is ≥3 μm; and / or the touch drying time of the film layer is ≤10 min.

7. The magnetic structure according to claim 1, characterized in that: A coating layer is also arranged on the film layer.

8. The magnetic structure according to claim 1, characterized in that: The soft magnetic alloy powder is Fe-based soft magnetic alloy powder.

9. The method for preparing a magnetic structure according to any one of claims 1 to 8, characterized in that: The following steps are involved: The resin is introduced into the pores of the magnetic body by vacuum pressure impregnation; and the resin forms a film layer on the surface of the magnetic body by separation operation.

10. An electronic device, characterized in that The invention comprises the magnetic structure described in any one of claims 1 to 8 or the magnetic structure prepared by the preparation method described in claim 9.

Citation Information

Patent Citations

  • Inductance element and manufacturing method thereof

    CN112927915A

  • Coil component and method for manufacturing coil component

    CN113963914A

  • Manufacturing method of compression molding inductor with high falling performance

    CN116453837A

  • R-fe-b based bond magnet and production thereof

    JP1995201620A

  • Composite porous body

    JP2007008762A